PERBANDINGAN HASIL BELAJAR FISIKA SISWA YANG MENGGUNAKAN MODEL PEMBELAJARAN KOORPERATIF TIPE GROUP INVESTIGATION DENGAN DISCOVERY INQUIRY DI SMA - Dewi Maynastiti; Vina Serevina; Anggara Budi Susila (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
The purpose of this research is to know the comparison of learning outcomes physics student using cooperative learning model of type Group Investigation with Discovery Inquiry. The research is conducted in SMAN 2 Bekasi on February-April 2015. The samples were 38 students who have similar conditions. The samples are X MIA 5 as experiment class 1 and X MIA 6 as experiment class 2. The method used in this research is quacy experimental design. The instrument of this research is multiple choice formed with 30 questionare. Requirement test uses normality test with Chi-square since Ï‡2count (5,188) â‰¤ Ï‡2table (12,59159) on experiment class 1 and Ï‡2count (2,649) â‰¤ Ï‡2table (12,59159) on experiment class 2, than the conclusion is that the data is distributed normal. On homogeneity test for Î±=5% and n=38 obtained Fcount (1,348) Ftable (1,76) therefore the data obtained are homogeneous. Based on hypothesis test using t-test, shown that tcount (1,86) and ttable (1,66571) at significance level Î±=5% with dk = 38+38-2=74. Because of tcount > ttabel, then H0 is rejected and Ha is accepted. So it can be concluded that the results of outcome physics model of Group Investigation is higher than the results of outcome physics learning on Discovery Inquiry. Keywords: Group Investigation, Discovery Inquiry, outcomes physics learning.